No baseline strength differences between female recreational runners who developed an injury and injury free runners during a 16-week formalized training program. (November 2018) - Torp, Danielle M.; Donovan, Luke; Gribble, Phillip A.; Thomas, Abbey C.; Bazett-Jones, David M.; Beard, Megan Q.
Abstract: Objective: To identify whether baseline differences in hip and knee isometric strength exist among female runners who sustained a running related injury (RRI) and those that remained injury-free during a 16-week formalized training program. Design: Prospective Cohort. Setting: Laboratory Setting. Participants: 54 healthy female recreational runners enrolled in a formalized training program for half or full marathon. At the conclusion of the program, 50 female runners (age: 39.1 ± 9.4 years; height: 165.3 ± 7.4 cm; mass: 64.8 ± 11.9 kg) were included in analysis. Main outcome measures: Peak isometric torque of knee flexion and extension, hip flexion and extension, and hip abduction and external rotation were compared between runners who sustained an RRI and injury-free (INJF) runners. Results: 15 of the 50 participants developed an RRI during the observational period, no between groups differences existed for any demographic variable. Hip and knee isometric strength was not different prior to the start of a 16-week formalized training program between runners who sustained an RRI and those that remained injury-free. Conclusions: Hip and knee weakness does not appear to be a baseline characteristic among female recreational runners who sustained an RRI or remained uninjured while training for a half or full marathon. Highlights: Hip and knee strength is compromised in runners with running related musculoskeletal injuries. Strength is not found to be a baseline characteristic of injury development in healthy runners before starting a training program. Assessment of strength should be limited to post-injury evaluation to guide rehabilitation programs.